The Role of Prudent Accounting in The Achievement of Leadership in Institutions of Higher Education From The Perspective Of The Members Of The Accounting Faculty At King Khalid University - Tayed Ali Ahmed, Roukaya (Finance and Business Economies Review, 2019)
The study seeks to explain the role played by the application of the lean accounting tools in theachievement of leadership by focusing on two tools, namely continuous improvement and employee satisfaction, because there is many tools of lean accounting The study was based on the method of induction in addition to the analytical approach, and the study reached a series of results, lean accounting is a bridge to reach leadership and it achieves a competitive advantage as well as a new innovation in the performance of educational institutions. The study recommended a set of recommendations, the most prominent of which is the consolidation of the quality strategy that leads to the need to add continuous improvements and that future studies should be done to measure the role of lean accounting tools graceful not used in the study to achieve leadership.